Characteristics of wind-induced displacement of super-large cooling tower based-on continuous medium model wind tunnel test. Issue 180 (September 2018) - Zou, Yun-feng; He, Xu-hui; Jing, Hai-quan; Zhou, Shuai; Niu, Hua-wei; Chen, Zheng-qing
Abstract: A cooling tower is a wind-sensitive structure, and wind loading is used as the control load for its design. In this study, the displacement characteristics of a large concrete cooling tower with respect to a turbulent wind is investigated by using a continuous medium model wind tunnel test. Firstly, based on the similarity relations of the continuous medium model for the cooling tower, which were derived and verified in the present study, a continuous medium model with a geometrical scale of 1:400 is designed and processed for a 200 m high cooling tower at a nuclear power plant in China. Subsequently, wind tunnel tests are carried out to measure the wind-induced displacement using a high-precision laser displacement sensor. Based on the results, the displacement and characteristics of the power spectra of some typical measurement points are analyzed. The analysis result indicates that the continuous medium model can accurately simulate the similarity relations of mass, stiffness, and damping. It is also found that the maximum displacement occurs in the windward side of the throat, and the size is about 20% of the throat thickness. In addition, background response plays a major role in the total displacement response, and the dynamic amplification effect is not obvious. The mean dynamic amplification coefficient is 1.02, which is slightly less than the value of 1.05 specified in VGB-R 610Ue, 2010. At the same time, the test result shows that gust loading factor decreases with increase in height, which is consistent with VGB-R 610Ue, 2010, and the mean value is slightly less than the specified value. Highlights: We derived and verified the similarity relations of continuous medium model for cooling tower, and a continuous medium model with geometrical scale of 1:400 was designed and processed precisely for a 200 m high cooling tower. Test result indicates continuous medium model can accurately satisfies the simulation of similarity relation of mass, stiffness and damping. The max displacement happens in windward side of the throat, and the size is about 20% of the throat thickness. Background response plays a major role in the total displacement response and the dynamic amplification effect is not obvious, and the mean dynamic amplification coefficient is 1.02. Test result shows that gust loading factor decreases with the increasing of height, and the mean value is slightly less than the specified value.